Pelikula a documentary on Philippine film - Guillen, Laurice; Lumbera, Bienvenido; Sotto, Agustin (Tuklas sining series, 1989)
Traces the history of moviemaking in the Philippines from the 1930's to the present, representing the major commercial genres--musical, melodrama, comedy and action--as well as the new cinema and contemporary alternative films.